The Influence of Achievement Motivation and The Need for Regular Life on The Formation of The Islamic Personality of IAIN Kudus - Retnanto, Agus; Firdiansyah, Bahtiar; Fah, Lay Yoon (Universitas Muhammadiyah Purwokerto, 2023)
The Influence of Achievement Motivation and The Need for Regular Life on The Formation of The Islamic Personality of IAIN Kudus